Overview on locally advanced breast cancer: defining, epidemiology, and overview on neoadjuvant therapy - Yalcin, B. (Experimental Oncology, 2013)
According to the analysis on locally advanced breast cancer (LABC) from all breast cancer cases recorded in Surveillance Epidemiology and End Results database between the years 1992 - 1999 in the United States, the incidence of LABC were found to be 4,6 % of all female breast cancers. Clinically, when breast cancer has advanced locoregionally but has not yet spread outside of the breast and regional lymph nodes, it is considered LABC. LABC includes breast cancers that have evidence of a large mass, involve the skin of the breast or the underlying muscles of the chest wall, and cancers that have infiltrated into the local lymph nodes. The prognosis of patients with LABC is relatively poor, with 5-year survival rates less than 50 %. Because the incidence of LABC is very low, there are not many studies comparing neoadjuvant chemotherapy regimens in the literature. In management of LABC, initial therapy should be systemic neoadjuvant chemotherapy, aiming pCR. Anthracycline-based chemotherapy regimens are frequently recommended as the standard primary neoadjuvant chemotherapy for the treatment of LABC. Today the optimal duration of neoadjuvant chemotherapy is unknown. Neoadjuvant endocrine therapy is considered an option for patients with honnone receptor-positive LABC. Ongoing clinical trials are now under way to evaluate the use of novel targeted agents in the neoadjuvant treatment of LABC.